Factors That Account For Low Enrollment In Community-Based Senior High Schools In The Ashanti Region Of Ghana (International Journal of Scientific Research and Management (IJSRM), 2019)
The study was to explore the factors that account for low enrolments in senior high schools in the Ashanti Region of Ghana. The purpose of the study was to investigate the factors that account for low enrolments in the community-based senior high school in the Ashanti Region of Ghana. The purpose of the study was to investigate socio-economic factors, school related factors, geographical factors and individual characteristics that influence enrolments, participation, retention, attendance, progression and dropout in community-based senior high schools in Ashanti Region of Ghana. The purposive and quota sampling were used to select a sample size of 120 respondent make up of 10 heads, 10 Districts Directors of Education, 10 PTA chairmen and 90 parents of sampled schools. The instruments used to collect data from the respondents were the questionnaire for heads, structured interview guide for parents. PTA Chairmen and the District Directors of GES and observation guide on school building and furniture. The reliability co-efficient of the study was 0.82. The co-efficient is high enough and hence the items were deemed reliable for the study. Data were analysed by the use of frequencies, percentages and apparent cohort method. The finding of the study indicated that most of the sampled senior high schools do not have school bus to convey day students to and from schools. The sample senior high schools do not have workshops for all programmes, classrooms and standard science laboratories and science equipment to enhance academic work.